Legal System in the Perspectives of H.L.A Hart and Lawrence M. Friedman - Ab. Halim, Mustafa ‘Afifi; Amni, Shabrina Zata; Maulana, Mufti (Peradaban Journal of Law and Society, 2023)
This article presents an analysis of the views of H.L.A Hart and Lawrence Friedman on the legal system from different perspectives. Through a comparative approach, this article identifies key concepts introduced by both scholars and highlights points of convergence and divergence between them. The research methodology used is a literature review, where primary and secondary sources, including . written works, books, and scientific articles authored by Hart and Friedman, are collected and analysed.. The author then conducts a comparative analysis to gain a deeper understanding of their views. The research findings indicate that H.L.A Hart views the legal system as a combination of primary and secondary rules that play a role in maintaining social order. On the other hand, Lawrence M. Friedman considers it as a product shaped by  contextual and historical factors. Their perspectives provide a comprehensive understanding of the nature and function of the legal system.  This article has implications for legal theory and serves as a foundation for further research on the legal system within the context of Hart and Friedman's views.